Analysis Of The Teacher's Perception Of The Headmaster's Leadership And Supervision Of Teacher Performance In Elementary School - Yusella, Yeni; Aini, Muntaza Nur; Saputro, Uung Gondo; Maisyaroh, Maisyaroh (STKIP Yapis Dompu, 2022)
This investigation was conducted correctly and was inspired by the headmaster's leadership in carrying out his responsibilities. This research aims to identify teachers' impressions of leadership by examining the headmaster's leadership style, supervision, job motivation, and educational background. The collecting of data involves observation, documentation, and interviews. All the instructors at SDN Diniyo 3 Malang were observed and interviewed. The gathered information is subsequently examined, and conclusions are formed. If there is a positive relationship between teachers' perceptions of the headmaster's leadership style and supervision, work motivation, and educational background, and teacher performance, this can provide a framework for the relevant parties to be willing and able to pay more attention to these three factors so that the teacher performance of SDN Dinoyo 3 Malang increases and improves.